Modificações na anatomia e trocas gasosas em poáceas (Poaceae) C3, intermediárias e C4 sob sobreamento - Cruz, Alana Batista (2022)
C3 species are more generalist when compared to C4 plants, specialists, consequently, their leaves tend to be more plastic. To understand the evolutionary pathway of the C4 pathway, studies with intermediate species are becoming more and more attractive, in order to understand the transition from C3 to C4 with the aim of manipulating traits of agricultural interest. Thus, the present study aims to evaluate the phenotypic plasticity of photosynthetic and leaf anatomical characteristics in plants of Mesosetum loliiforme (Hochst. ex Steud.) Chase (C4), Homolepis isocalycia (G. Mey.) Chase (intermediate), Homolepis longispicula (Döll) Chase (intermediate) and Homolepis glutinosa (Sw.) Zuloaga & Soderstr. (C3) in three shading conditions: Shade Cloth (SC), Insulfilm (I) and Direct Sunlight (DS). The experimental design was entirely randomized (DIC) in a 4x3 factorial scheme. Gas exchange was evaluated by obtaining intercellular CO2 concentration curves by photosynthetic rate and photosynthesis response curves to irradiance using the LiCor LI-6400-XT infrared gas analyzer, in addition, to serial transverse and longitudinal leaf sections for making permanent slides and anatomical characterization. The data obtained were submitted to analysis of variance (ANOVA) followed by Tukey's test (P < 0.05) using the R Studio software. The intermediate species have similar characteristics to C3 and C4 that allow for anatomical and physiological adjustments in response to shading. Light influenced the anatomy of H. longispicula leaving it more similar to C3, as for photosynthetic parameters, these were more similar to C4. All four species showed plasticity in response to light environments, especially between direct sunlight and shade cloth.